A squiggly story - Larsen, Andrew, 1960- (Kids Can Press, 2016)
A young boy wants to write a story, just like his big sister. But there's a problem, he tells her. Though he knows his letters, he doesn't know many words. His sister patiently explains, "Every story starts with a single word and every word starts with a single letter. Why don't you start there, with a letter?" So the boy tries. He writes a letter. An easy letter. The letter I. And from that one skinny letter, the story grows, and the little boy discovers that all of us, including him, have what we need to write our own perfect story.